2016
DOI: 10.1007/s00592-016-0864-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for prolonged QT interval and QT dispersion in patients with type 2 diabetes

Abstract: AimsProlonged QT interval is associated with cardiac arrhythmias and sudden death. The present study determined the prevalence of prolonged QT interval and QT dispersion and defined their clinical and metabolic predictors in patients with type 2 diabetes.Methods Cross-sectional study included 501 patients with type 2 diabetes. A standard 12-lead electrocardiogram was recorded. QT corrected for heart rate (QTc) >440 ms and QT dispersion (QTd) >80 ms were considered abnormally prolonged. QTc ≥ 500 ms was conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 47 publications
8
75
1
2
Order By: Relevance
“…These findings were in accordance with the previous studies as the prevalence of high QTc duration and QTc dispersion ranged from 15.4 to 67% for QTc and from none to 33% for QTc dispersion 23-26. Ninkovic et al mentioned about the GV as a risk factor of prolonged QT and QT dispersion 27. They used the mean amplitude of glycemic excursion (MAGE) to represent the GV.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings were in accordance with the previous studies as the prevalence of high QTc duration and QTc dispersion ranged from 15.4 to 67% for QTc and from none to 33% for QTc dispersion 23-26. Ninkovic et al mentioned about the GV as a risk factor of prolonged QT and QT dispersion 27. They used the mean amplitude of glycemic excursion (MAGE) to represent the GV.…”
Section: Discussionsupporting
confidence: 88%
“…Li et al claimed that microalbuminuria was the only diabetic microvascular complication related to QTc prolongation other than retinopathy and nephropathy 26. On the other hand Ninkovic et al showed a significantly higher prevalence of retinopathy and polyneuropathy among patients with high QTc duration 27. In our study, we couldn’t find any relation between microvascular complications and QT parameters.…”
Section: Discussioncontrasting
confidence: 80%
“…[53] Recently, Ninkovic et al found that sulfonylurea exposure was an independent risk factor for QT interval prolongation in persons with T2DM. [55] In contrast, Tentolouris et al found that neither QT interval duration nor dispersion was significantly longer in sulfonylurea vs. insulin users. [56] Yet, the latter two studies comingled users of different sulfonylureas into a single exposure group.…”
Section: Proarrhythmic and Antiarrhythmic Actions Of Sulfonylureasmentioning
confidence: 99%
“…QT prolongation is associated with cardiac arrhythmias and sudden death 77. Its pathogenesis is multifactorial, but includes an imbalance in cardiac sympathetic innervation and left-ventricular hypertrophy, as is often seen in CAN 78…”
Section: Clinical Manifestations and Consequences Of Canmentioning
confidence: 99%